2012
DOI: 10.1159/000337232
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of S-1 in Patients in Whom Inulin Clearance Was Measured

Abstract: Objective: This pharmacokinetic study of S-1 was conducted in patients in whom glomerular filtration rate (GFR) was directly measured to explore the possibility of adjusting the S-1 dose on the basis of GFR in patients with normal or nearly normal renal function. Methods: S-1 was given to 12 patients twice daily for 28 consecutive days followed by 14 days of rest, repeated every 6 weeks. GFR was measured on the basis of inulin clearance (CLin) before the first day of treatment. Results: The area under the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…As previously reported, our study demonstrated a correlation between renal function and clearance of CDHP. Of note, we performed sampling for pharmacokinetic investigation on day 8, when the plasma concentration of CDHP reached a steady state .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As previously reported, our study demonstrated a correlation between renal function and clearance of CDHP. Of note, we performed sampling for pharmacokinetic investigation on day 8, when the plasma concentration of CDHP reached a steady state .…”
Section: Discussionsupporting
confidence: 90%
“…Of note, we performed sampling for pharmacokinetic investigation on day 8, when the plasma concentration of CDHP reached a steady state . In contrast, previous studies performed sampling for pharmacokinetics on the first day of S‐1 administration, prior to CHDP reaching a steady state . Moreover, previous studies included few patients with moderate or severe renal dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Renal function may also affect the deviation of the plasma concentration of S-1. Over 50% of 5-chloro-2,4-dihydroxypyrimidine is excreted in urine so that the area under the curve of the serum concentration of 5-chloro-2,4-dihydroxypyridine and tegafur is significantly related to creatinine clearance [25,26,27]. Creatinine clearance in the S-1 arm and the serum creatinine level in the GS arm were statistically higher in the low-dose group than in the high-dose group, which might affect the incidences of adverse events between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…S-1 consists of three drugs: tegafur (a prodrug of fluorouracil), gimeracil (which inhibits fluorouracil degradation), and oteracil (which reduces gastrointestinal toxicity caused by fluorouracil phosphorylation) [13]. Once renal function deteriorates due to CDDP, the concentration of fluorouracil increases, leading to increased fluorouracil toxicity (because gimeracil is excreted in urine via the kidney) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Once renal function deteriorates due to CDDP, the concentration of fluorouracil increases, leading to increased fluorouracil toxicity (because gimeracil is excreted in urine via the kidney) [13]. As a result, it may be necessary to avoid the use of S-1, the key medication, in certain patients.…”
Section: Discussionmentioning
confidence: 99%